ACADEMIC ACHIEVEMENT OF ADOLESCENTS FROM SELECTED ETHNOCULTURAL GROUPS IN CANADA: A STUDY CONSISTENT WITH JOHN OGBU’S THEORY - Samuel, Edith; Krugly-Smolska, Eva; Warren, Wendy (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2001)
ABSTRACT. This paper analyses the academic achievement of adolescents in selected ethnocultural groups in Canada. Specifically, the article, a part of a larger study, is an analysis of the academic performance of adolescents from the Caribbean, Chinese, East European, Latin American, South Asian and Canadian groups. In the larger study 1,954 students were surveyed and 131 were interviewed in schools in Toronto and Vancouver. The findings in the article, consistent with John Ogbu’s theory, indicate that the majority of the students who belong to voluntary, as opposed to involuntary, minority ethnocultural groups excel in academic performance despite language barriers and racial discrimination. Few studies have been conducted on the academic achievement of selected ethnocultural adolescents. Therefore the purpose of this study was to (1) determine the academic achievement of selected ethnocultural adolescents and (2) demonstrate consistency with John Ogbu’s cultural-ecological theory of voluntary minority groups in the Canadian context. RÉSUMÉ. Cet article analyse les résultats scolaires d’adolescents appartenant à des groupes ethnoculturels choisis au Canada. En particulier, l’article, qui s’inscrit dans une étude plus vaste, analyse les résultats scolaires des adolescents appartenant à des groupes d’origine antillaise, chinoise, d’Europe de l’Est, d’Amérique latine, d’Asie du Sud et du Canada. Dans l’étude plus vaste, 1 954 élèves ont été étudiés et 131 ont été interrogés dans des écoles situées à Toronto et Vancouver. Les résultats de l’article, qui concordent avec la théorie de John Ogbu, révèlent que la majorité des élèves qui appartiennent à des groupes parmi les minorités ethnoculturels, volontaires plutôt qu’involontaires obtiennent d’excellents résultats scolaires malgré les d’obstacles linguistiques et la discrimination raciale. Peu d’études ont été menées sur les résultats scolaires d’adolescents appartenant à des groupes ethnoculturels choisis.2 C’est pourquoi le but de cette étude était (1) de déterminer les résultats scolaires d’adolescents appartenant à des groupes ethnoculturels donnés et (2) de corroborer la théorie culturelle-écologique de John Ogbu sur les groupes minoritaires volontaires dans le contexte canadien.